Mitigation of Environmental Stress-Impacts in Plants: Role of Sole and Combinatory Exogenous Application of Glutathione - Koh, Yi Sze; Wong, See Kiat; Ismail, Nor Hadiani; Zengin, Gokhan; Duangjai, Acharaporn; Saokaew, Surasak; Phisalprapa, Pochamana; Tan, Khang Wei; Goh, Bey Hing; Tang, Siah Ying (Frontiers in Plant Science, 2021)
Glutathione (GSH; γ-glutamyl-cysteinyl-glycine), a low-molecular-weight thiol, is the most pivotal metabolite involved in the antioxidative defense system of plants. The modulation of GSH on the plant in response to environmental stresses could be illustrated through key pathways such as reactive oxygen species (ROS) scavenging and signaling, methylglyoxal (MG) detoxification and signaling, upregulation of gene expression for antioxidant enzymes, and metal chelation and xenobiotic detoxification. However, under extreme stresses, the biosynthesis of GSH may get inhibited, causing an excess accumulation of ROS that induces oxidative damage on plants. Hence, this gives rise to the idea of exploring the use of exogenous GSH in mitigating various abiotic stresses. Extensive studies conducted borne positive results in plant growth with the integration of exogenous GSH. The same is being observed in terms of crop yield index and correlated intrinsic properties. Though, the improvement in plant growth and yield contributed by exogenous GSH is limited and subjected to the glutathione pool (GSH/GSSG; the ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG)) homeostasis. Therefore, recent studies focused on the sequenced application of GSH was performed in order to complement the existing limitation. Along with various innovative approaches in combinatory use with different bioactive compounds (proline, citric acid, ascorbic acid, melatonin), biostimulants (putrescine, Moringa leaf extract, selenium, humic acid), and microorganisms (cyanobacteria) have resulted in significant improvements when compared to the individual application of GSH. In this review, we reinforced our understanding of biosynthesis, metabolism and consolidated different roles of exogenous GSH in response to environmental stresses. Strategy was also taken by focusing on the recent progress of research in this niche area by covering on its individualised and combinatory applications of GSH prominently in response to the abiotic stresses. In short, the review provides a holistic overview of GSH and may shed light on future studies and its uses.